2020
DOI: 10.17576/pengurusan-2020-58-11
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Information and Communication Technology (ICT) Usage, Knowledge Sharing and Innovative Behavior among Engineers in Electrical and Electronic MNCs in Malaysia

Abstract: Innovative behavior is vital for organizations as competition based on innovation can serve as a basis for sustainable development, especially for multinational companies in the Electrical and Electronic sector in Malaysia. Grounded by the social cognitive theory, this study utilized a research framework examining ICT usage as a predictor of innovative behavior with knowledge sharing (knowledge giving and knowledge receiving) as mediating variables. A total of 309 engineers from multinational companies in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 69 publications
1
11
0
2
Order By: Relevance
“…Alhawary & Assistance (2017) found that KS has a significant positive relationship between KS and EP. However, Ibrahim et al (2020) found that ICT usage harms KS. The study also found that ICT usage had no direct relationship with KS.…”
Section: Mediating Role Of Knowledge Sharingmentioning
confidence: 98%
“…Alhawary & Assistance (2017) found that KS has a significant positive relationship between KS and EP. However, Ibrahim et al (2020) found that ICT usage harms KS. The study also found that ICT usage had no direct relationship with KS.…”
Section: Mediating Role Of Knowledge Sharingmentioning
confidence: 98%
“…For example, Islam and Ashif [31] indicated that ICT could facilitate collaborative work and knowledge transfer. Ibrahim et al [32], Mazzucchelli et al [33], Roberts [34] and Safdar et al [35] discovered that ICT enhances KS by reducing temporal and spatial barriers between people and improving access to knowledge. ICTs streamline the collection, storage, and sharing of knowledge on a scale that was impossible until recently, which strengthens the process and ability to share knowledge [31,33,34,36,37].…”
Section: Ict Usage and Knowledge Sharingmentioning
confidence: 99%
“…The third and fourth parts of the questionnaire corresponded to the OIC (3 items) and IB (3 items), respectively. We developed the 24 items considered in the questionnaire from a thorough literature review based on [14,20,29,32,44,57].…”
Section: Questionnaire Surveymentioning
confidence: 99%
“…Among both professional bureaucracies and operating adhocracies, a service firm manager's ability to improve workers' knowledgesharing intentions plays a role in ensuring successful knowledge management. Some research suggests that information technology infrastructures have no influence on knowledge-sharing intentions, such as Ibrahim [14] in manufacturing and Kucharska and Erickson [15] in various industries. However, in the service sector, such infrastructures do [10,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%